Security Psychology: New Perspectives From the COVID-19 Pandemic - Hopner V; Carr S; Young M; Nelson N; Hodgetts D (PsychOpen GOLD/ Leibniz Institute for Psychology, 2025)
In 1994, the United Nations human security taxonomy signaled a major shift from security as preservation of the nation-state towards a broader and more recent ‘decagonal’ model of human security (entailing everyday needs for personal, health, food, cyber, community, economic, national, environmental, political and, most recently, global security). Building on those foundations, this paper proposes a psychological theory of human security. The latter we propose is a question of ‘systems fit’ between everyday needs and priorities to official responses during crises like the COVID-19 pandemic. During COVID-19 lockdowns in 2021, across Australia and New Zealand, we asked N = 2,162 Australasians whether they had each type of security, how important each type was to them, and what each of the 10 sub-types of security meant to them. On face value, a pandemic is a primary threat to national public health. In everyday life, however, all 10 dimensions of human security remained salient and interconnected.
Keywords: Australia; Human Security; New Zealand; Security Psychology; Sustainable Livelihoods; United Nations